PENINGKATAN PERTUMBUHAN VEGETATIF DAN PRODUKSI BUAH TERUNG UNGU (Solanum melongena L.) DENGAN APLIKASI PUPUK ORGANIK - Utami, Hikmah Putri Wahyu; Defiani, Made Ria; Muksin, I Ketut (SIMBIOSIS, 2023)
E ggplant (Solanum melongena L.) is a horticultural product belong to the Solanaceae family . E ggplants ar e in great demand because cheap and lots of vitamin A, B a nd C . Along with increasing demand , eggpl ant production needs to be increased. Increasing eggplant production can be pursued by giving organi c fertilizer with the right concentration. This research was conducted in April-August 2021 at the Green House of the Biology Study Program, FMIPA Udayana U niversity. The research design used was a completely randomized design (CRD) with a 3x4 factorial pattern with 3 replications. The first factor is the type o f organik fertilizer (A) with compost (A1), cow manure (A2) and goat manure (A3). The second factor is the concentration of organik fertilizer (B) which is 0 g/polybag (control) (B0), 500 g/polybag (B1), 1,000 g/polybag (B2) and 1,500 g/polybag (B3). Param eters observed is p lant height , n umber of leaves , n umber of branches , f lower initiation time, a ge o f the plant at harvest , n umber of fruit crops, f ruit length, f ruit weight, and fruit diameter. Data were analyzed using Analysis of Variance (ANOVA) and cont inued with Duncan Multiple Range Test (DMRT) analysis. The r esults showed that the treatment of goa t manure and a concentration of 1,500 g could increase all research parameters. The combination of goat manure with a concentration of 1,500 g gave effective results on the growth and production of eggplant.